2022
DOI: 10.1186/s12873-022-00582-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of prognosis in elderly patients with sepsis based on machine learning (random survival forest)

Abstract: Background Elderly patients with sepsis have many comorbidities, and the clinical reaction is not obvious. Thus, clinical treatment is difficult. We planned to use the laboratory test results and comorbidities of elderly patients with sepsis from a large-scale public database Medical Information Mart for Intensive Care (MIMIC) IV to build a random survival forest (RSF) model and to evaluate the model’s predictive value for these patients. Methods C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…30 A machine-learning research constructed a good predictive model for 30-day mortality in sepsis and RDW was one of top five important factors. 31 Our study mainly concentrated on the septic shock patients and found the close relationship between RDW and prognosis. Pathophysiologic mechanisms underlying the association of RDW with mortality could be speculated based on current researches.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…30 A machine-learning research constructed a good predictive model for 30-day mortality in sepsis and RDW was one of top five important factors. 31 Our study mainly concentrated on the septic shock patients and found the close relationship between RDW and prognosis. Pathophysiologic mechanisms underlying the association of RDW with mortality could be speculated based on current researches.…”
Section: Discussionmentioning
confidence: 87%
“…Another retrospective analysis based on a public database illuminated that septic patients in the elevated level of RDW group had both higher rate of ICU mortality and hospital mortality 30 . A machine‐learning research constructed a good predictive model for 30‐day mortality in sepsis and RDW was one of top five important factors 31 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, if applying the Global Burden of Diseases, Injuries, and Risk Factors Study as the reference to compare with sepsis incidence, the incidence of sepsis can be as high as 677.5 cases per 100,000 persons worldwide ( 45 ). Previous research shows that RDW is a useful prediction of mortality in adult sepsis patients ( 46 , 47 ). In a meta-analysis from 2020, the result of synthesis of 11 included studies indicated that high-level RDW was associated with mortality (HR = 1.14, 95% CI 1.09–1.20, Z=5.78, P <.001).…”
Section: Discussionmentioning
confidence: 99%
“…The APS-III scale has been widely used in the medical community as an important tool for predicting the risk of death prediction in ICU patients. In a recent study on prognosis prediction of ICU patients ( Zhang et al, 2022 ), the results showed that the independent receiver operating characteristic curve (ROC) curve results of the APS-III scale were superior compared to those of the SAPS-II, LODS, OASIS, and SOFA scales, indicating that the former has a more promising accuracy in the prognosis prediction of critically ill patients. Thus, the results of the APS-III scale were used to evaluate the prognosis of patients in this study Figure 2 .…”
Section: Methodsmentioning
confidence: 99%